Akumulasi Mn dalam Cairan Tubuh Ligumia nasuta (Say, 1817) di Sungai Ciputri Bandung Jawa Barat - Endah Kartikawati; Andhika Puspito Nugroho (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2016)
Ciputri upriver, Bandung, West Java has polluted by heavy metal Mn coming from cow feces in the Cikidang village. The aim of research is to study Mn accumulation in the Eastern Pondmussel Ligumia nasuta (Say, 1817). Mn contents in the water, extra pallial fluid, and hemolymph were determined by Atomic Absorbance Spectrophotometer (AAS). The mussels were collected at day 0, 1, and 6 after transplantation at 3 stations: before, near, and after pollution sources. The results show that the highest Mn accumulation was in the extra pallial fluid (1,21 mmol kg-1 ww) at station 2, day 6. It showed that exposure of Mn to the mussels taken place via water.